2020
DOI: 10.3390/w12020382
|View full text |Cite
|
Sign up to set email alerts
|

Human Activities and Climate Variability Affecting Inland Water Surface Area in a High Latitude River Basin

Abstract: Spatiotemporal changes in the surface area of inland water bodies have important implications in regional water resources, flood control, and drought hazard prediction. Although inland water bodies have been investigated intensively, few studies have looked at the effect of human activities and climate variability on surface area of inland waters at a larger scale over time and space. In this study, we used MODIS (MOD13Q1) images to determine water surface area extent at 250 m spatial resolution. We then appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Other important aspect of urban water availability is the declining inland surface waterbodies (urban wetlands such as canals, ponds, or constructed inland fresh waterbodies) and their littoral zones due to urbanization (Vörösmarty et al, 2000;Moss, 2008;Feng et al, 2010;Veldkamp et al, 2017;Chen et al, 2020). Mukherjee et al (2018Mukherjee et al ( , 2020 showed that borough wise declining rate of wetlands was higher in the main city areas whereas the peripheral areas lost comparatively less.…”
Section: Water Availabilitymentioning
confidence: 99%
“…Other important aspect of urban water availability is the declining inland surface waterbodies (urban wetlands such as canals, ponds, or constructed inland fresh waterbodies) and their littoral zones due to urbanization (Vörösmarty et al, 2000;Moss, 2008;Feng et al, 2010;Veldkamp et al, 2017;Chen et al, 2020). Mukherjee et al (2018Mukherjee et al ( , 2020 showed that borough wise declining rate of wetlands was higher in the main city areas whereas the peripheral areas lost comparatively less.…”
Section: Water Availabilitymentioning
confidence: 99%
“…Twenty-nine percent of studies concentrating on the East of China focus on a biosphere-related topic. Most studies concentrate on landscape change in general [123,196] or wetland monitoring in particular [74,155,188,222,224,232] and base their results on multi-temporal Landsat observations or Landsat-based time series. The exceptions are the SAR-based approach by Ref.…”
Section: Asiamentioning
confidence: 99%
“…The multi-year average temperature is 4.5 • C, and the multi-year average rainfall is 400-500 mm [28,[30][31][32]. According to previous studies in this region, the water environment in the Momoge National Nature Reserve was found to be better than that of the lakes in the Chagan Lake area [33,34]. However, the lakes in the Momoge National Nature Reserve are still in a state of light eutrophy.…”
Section: Sampling and Sitesmentioning
confidence: 99%